2017
DOI: 10.3390/s17122783
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudorange Measurement Scheme Based on Snapshot for Base Station Positioning Receivers

Abstract: Digital multimedia broadcasting signal is promised to be a wireless positioning signal. This paper mainly studies a multimedia broadcasting technology, named China mobile multimedia broadcasting (CMMB), in the context of positioning. Theoretical and practical analysis on the CMMB signal suggests that the existing CMMB signal does not have the meter positioning capability. So, the CMMB system has been modified to achieve meter positioning capability by multiplexing the CMMB signal and pseudo codes in the same f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The Taylor-iteration method uses an iterative method to sole the set of hyperbolic equations and estimate of the position of an MS. 8 The procedure is started with an initial guessed coordinate values ( x 0 , y 0 ) and determines the local linear least-square solution as the deviations at each of iteration. In every iteration, x 0 and y 0 are set to be x = x 0 + Δ x and y = y 0 + Δ y , the whole process is repeated until the deviation Δ x and Δ y are sufficiently small.…”
Section: Localization Model Using Tdoamentioning
confidence: 99%
See 2 more Smart Citations
“…The Taylor-iteration method uses an iterative method to sole the set of hyperbolic equations and estimate of the position of an MS. 8 The procedure is started with an initial guessed coordinate values ( x 0 , y 0 ) and determines the local linear least-square solution as the deviations at each of iteration. In every iteration, x 0 and y 0 are set to be x = x 0 + Δ x and y = y 0 + Δ y , the whole process is repeated until the deviation Δ x and Δ y are sufficiently small.…”
Section: Localization Model Using Tdoamentioning
confidence: 99%
“…Jiang et al 7 deals with source localization with TDOA measurements in two-dimensional (2D) scenarios. The Taylor series method 8 and Chan’s method 9 are the basic TDOA localization methods. The Taylor series method linearizes the set of equations by Taylor series expansion, then uses an iterative method to solve the system of linear equations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the positions had a mean precision of ±22 m with an SD of 49 m. Ground-based TDoA location systems can experience substantial noise due to multipathing where the time differences are exaggerated due to signal paths that are not line-of-sight, this is the kind of error we seek to address in this study. The examined localization method uses TDoA among four fixed receivers to estimate the origin of the transmission, the two most basic analytical methods are the Taylor series method [17] and Chan method [3] that can localize objects with minimal error in the absence of multipathing. To address noise in TDoA location estimates machine learning-based methods are introduced for localization in an arbitrarily complex system, current approaches to this problem falls into two main methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the positions had a mean precision of ±22 m with an SD of 49 m. Ground-based TDoA location systems can experience substantial noise due to multipathing where the time differences are exaggerated due to signal paths that are not line-of-sight, this is the kind of error we seek to address in this study. The examined localization method uses TDoA among four fixed receivers to estimate the origin of the transmission; the two most basic analytical methods are the Taylor series method [18] and Chan method [3] that can localize objects with minimal error in the absence of multipathing. To address noise in TDoA location estimates, machine learning-based methods are introduced for localization in an arbitrarily complex system.…”
Section: Introductionmentioning
confidence: 99%